Pulmonary rehabilitation in connective tissue disease-associated interstitial lung disease: A systematic review - Seleoglu, Irem; Demirel, Aynur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background and aim: Interstitial lung disease (ILD) is the major contributor to mortality in between chronic lung diseases. ILD originates from voluminous pathophysiological factors. One of the reasons is connective tissue diseases (CTD). According to experts, patients with CTD-ILD may have a stable disease activity and not need conventional treatment. Also, with pulmonary rehabilitation (PR), these patients may benefit from improving clinical outcomes and regression in mortality. However, the characteristics of these patients and whether they have stable disease activity in practice are not known. Methods: The systematic review was performed via the AI-powered tool with six databases to conduct literature research. The methodologic quality of the studies, risk of bias, and level of evidence were assessed. Results: According to the final four included studies PR benefit moderate levels of evidence for lung functions and diffusion capacity, functional capacity, quality of life, dyspnea severity, and fatigue level. However, there was limited evidence for respiratory, and peripheral muscle strength for CTD-ILD patients. Conclusions: The literature shows that the use of PR for CTD-ILDs wasn’t widespread. Our findings suggest that PR can be used in CTD-ILDs to recover clinical parameters like, lung functions, quality of life, dyspnea severity, and fatigue level. More comprehensive studies should be conducted to reveal the effect of the PR in the evidence-based frame.